Onde rico não mora: reflexões sobre direito à moradia e à cidade a partir da experiência da Vila Oliveira - Alcântara, Rafaela Cavalcanti de (2016)
The present dissertation takes as its starting point the eviction of Vila Oliveira - a community that was placed in Recife, Pernambuco -, which was carried out in November 2012 amid a context of real estate speculation and urban land dispute that arose in the area. The eviction affected more than twenty families that had been living for decades in the community, demolished houses, and left people homeless. In this sense, the research aims to analyze categories such as work, struggle, and the right to housing and to the city in order to obtain a perspective of them from the experience of people who experienced violations of such rights. The field research was inspired by Anthropology, more specifically by Ethnography, in order to access information and perspectives that would not be obtained through quantitative surveys or the application of questionnaires. The research work was guided by the speeches and perceptions of the affected inhabitants and therefore seeks to show the effects of a legal decision on the path and daily life of the working class. The first chapter emphasized the development of the community, presenting Vila Oliveira and making considerations about the establishment of its inhabitants in the area, changes carried out in the environment, construction of houses, and development of work, housing, and neighborhood relationships. The second chapter is dedicated to analyzing the eviction and demolition of the houses. Thus, it approached the execution of the possession order, debated its procedural backgrounds, and, also, discussed the specific legal decision that resulted in the eviction. In addition, the chapter also evaluated the perception that the affected people have of the Law, the Justice, and the Judiciary Branch, ending with a discussion about Capitalism, Urbanism, and the Law. Finally, the third and final chapter intended to discuss the changes in the journey and in the relations developed by the residents who started to live around ten kilometers from where they used to live before, in apartments offered by the government and located in a housing complex located in a neighborhood far from the downtown of Recife. With that, an analysis was made regarding what would “housing” mean to people evicted from places where they developed their social relationships for years and about how there are specific characteristics related to social class in the various possibilities of residing in a city. The information gathered in the field research were theoretically analyzed based on (i) authors that approach the Urbanism issue from a historical materialist framework, such as Henri Lefebvre and David Harvey; (ii) authors that discuss the Brazilian industrialization and/or urbanization issue, seeking to understand its idiosyncrasies, such as Francisco de Oliveira, Lúcio Kowarick, Ermínia Maricato, and Raquel Rolnik; (iii) Marxist-based studies concerning the reproduction of capitalism and the role of the State and the Law in such process.